Interaction of cationic liposomes and their DNA complexes with monocytic leukemia cells - Pires, Pedro (1999)
Cationic liposomes complexed with DNA have been used extensively as non-viral vectors for the intracellular delivery of reporter or therapeutic genes in culture and in vivo. We examined the relationship between the characteristics of the lipoplexes, their mode of interaction with monocytic THP-1 cells and their ability to transfect these cells. We determined the size and [zeta] potential of cationic liposomes (composed of 1,2-dioleoyl-3-(trimethylammonium) propane (DOTAP) and its mixtures with neutral lipids), and lipoplexes at different (+/-) charge ratios. As the (+/-) charge ratio of the lipoplexes decreased to (1/1), a significant reduction in [zeta] potential and an increase in size was observed. The increase in size resulted from fusion between liposomes promoted by DNA, as demonstrated by a lipid mixing assay, and from aggregation of the complexes. Interaction of liposomes and lipoplexes with THP-1 cells was assessed by monitoring lipid mixing ([`]fusion') as well as binding and cell association. While no lipid mixing was observed with the 1/2 (+/-) lipid/DNA complexes, lipoplexes with higher (+/-) charge ratios underwent significant fusion in conjunction with extensive cell binding. Liposome binding to cells was dependent on the positive charge of the liposomes, and their fusion could be modulated by the co-lipid. DOTAP/phosphatidylethanolamine (1:1) liposomes fused with THP-1 cells, unlike DOTAP/phosphatidylcholine (1:1) liposomes, although both liposome types bound to the cells to a similar extent. The use of inhibitors of endocytosis indicated that fusion of the cationic liposomes with cells occurred mainly at the plasma membrane level. The presence of serum increased the size of the cationic liposomes, but not that of the lipoplexes. Low concentrations of serum (3%) completely inhibited the fusion of cationic liposomes with cells, while inhibiting binding by only 20%. Our results suggest that binding of cationic liposomes and lipoplexes to cells is governed primarily by electrostatic interactions, whereas their fusion is regulated by the lipid composition and sterically favorable interactions with cell surface molecules. In addition our results indicate no correlation between fusion of the lipoplexes with the plasma membrane and the levels of transfection.